Abu Hanifah’s Legal Reasoning on Liwath: A Reflection on LGBT in Indonesia - Muhammad Sabilal Alif; Abdul Wahab (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
This research explores Imam Abu Hanifah’s legal perspective on liwath (homosexual acts) and assesses its relevance to contemporary LGBT issues in Indonesia. Islam, as a religion of rahmatan lil alamin, clearly prohibits all forms of sexual deviation, with liwath being unanimously declared haram by Islamic scholars. However, there is ikhtilaf (difference of opinion) among scholars regarding the appropriate level of uqubah (punishment) for such acts. Imam Abu Hanifah holds that both the perpetrator and the recipient of liwath should be subjected to ta'zir punishment a discretionary penalty determined by the state or ruling authority rather than the fixed hudud penalties applied to zina (fornication). The study has two main objectives: (1) to explore Imam Abu Hanifah’s opinion and legal method (istinbath) in determining the punishment for liwath; and (2) to examine the relevance of this opinion to Indonesia’s context, especially in light of LGBT rights. Using a normative juridical approach through library research, the study finds that Imam Abu Hanifah based his opinion on hadith and reasoned legal interpretation, avoiding qiyas (analogy) with zina due to fundamental differences in the acts. The thesis concludes that while Imam Abu Hanifah’s views are consistent within the framework of Islamic jurisprudence, their application in Indonesia today is limited. This is due to Indonesia’s identity as a nation-state rather than a religious state, and its constitutional commitment to human rights, including protection for LGBT individuals. Thus, direct implementation of classical ta'zir sanctions would conflict with modern legal and human rights standards.